Tax Compliance at National Level - Brezeanu, Petre; Dumiter, Florin; Ghiur, Rodica; Todor, Silvia Paula (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2018)
Throughout this study, we have shown the influence factors generating asignificant impact on taxpayers' tax behavior. We also analyzed the literature in the field,and the categories of factors that have a significant influence. Consequently, we haveassigned a macroeconomic indicator in Romania, in an attempt to quantify the factors ofinfluence. In this regard, we have built an econometric model of multifactorial regressionand we have determined the impact of some elements such as: poverty, labor productivity,population confidence in state authorities, gross domestic product per capita on fiscalbehavior, which was estimated through the proxy variable: tax rate. The empirical resultsobtained as a result of the multiple regression showed that there is a negative correlationbetween the fiscal behavior of the taxpayer, namely the tax compliance and the financialcapacity, the labor productivity and the confidence the taxpayer has in the state authorities,while the behavior of the taxpayer the gross domestic product per capita we identify apositive correlation.